2014
DOI: 10.1111/apa.12749
|View full text |Cite
|
Sign up to set email alerts
|

Orthodontic widening of the palate may provide a cure for selected children with therapy‐resistant enuresis

Abstract: Orthodontic widening of the palate may be curative in a subgroup of children with therapy-resistant enuresis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 17 publications
1
24
0
Order By: Relevance
“…Furthermore, we found that children who respond to RME have larger nasal airway volume at baseline, which may be taken as further support for this hypothesis. 13 We also concluded that RME does increase the nasal volume and airflow, which coincides with the findings in other studies. [14][15][16][17][18][19] Further, our findings concluded a significant correlation between the reduction of NE and increase in nasal volume after RME treatment, which indicates a strong connection between nasal volume and incidence of NE.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, we found that children who respond to RME have larger nasal airway volume at baseline, which may be taken as further support for this hypothesis. 13 We also concluded that RME does increase the nasal volume and airflow, which coincides with the findings in other studies. [14][15][16][17][18][19] Further, our findings concluded a significant correlation between the reduction of NE and increase in nasal volume after RME treatment, which indicates a strong connection between nasal volume and incidence of NE.…”
Section: Discussionsupporting
confidence: 92%
“…The long-term cure rate after 1 year was 18/30 (60%), whereas 12/30 (40%) had no long-term response (data published previously). 13 The transverse maxillary expansion was 4 6 1 mm (mean 6 standard deviation [SD]) (T0-T1), which declined to 2.3 6 0.85 mm (mean 6 SD) 6 months postretention (T0-T2) (P , .001). Thus, the mean transverse relapse from T1 to T2 at the first molar region was 1.7 6 0.95 mm.…”
Section: Resultsmentioning
confidence: 96%
“…5 Responders have also been found to have larger nasal airway dimensions. 23 None of the children in the current study sample suffered from upper airway obstructions.…”
Section: Discussionmentioning
confidence: 88%
“… 12 , 31 , 33 , 52 Several treatment options are available for nocturia, depending on the underlying cause. 6 , 31 , 71 , 72 This review shows that both adherence to nocturia treatment and outcomes are complex and intertwined. Nonadherence to nocturia treatment is common.…”
Section: Discussionmentioning
confidence: 99%